A Minimal Membrane Metal Transport System: Dynamics and Energetics of mer Proteins. Issue 6 (13th November 2019) - Hwang, Hyea; Hazel, Anthony; Lian, Peng; Smith, Jeremy C.; Gumbart, James C.; Parks, Jerry M.
Abstract : The mer operon in bacteria encodes a set of proteins and enzymes that impart resistance to environmental mercury toxicity by importing Hg 2+ and reducing it to volatile Hg(0). Because the reduction occurs in the cytoplasm, mercuric ions must first be transported across the cytoplasmic membrane by one of a few known transporters. MerF is the smallest of these, containing only two transmembrane helices and two pairs of vicinal cysteines that coordinate mercuric ions. In this work, we use molecular dynamics simulations to characterize the dynamics of MerF in its apo and Hg 2+ ‐bound states. We find that the apo state positions one of the cysteine pairs closer to the periplasmic side of the membrane, while in the bound state the same pair approaches the cytoplasmic side. This finding is consistent with the functional requirement of accepting Hg 2+ from the periplasmic space, sequestering it on acceptance, and transferring it to the cytoplasm. Conformational changes in the TM helices facilitate the functional interaction of the two cysteine pairs. Free‐energy calculations provide a barrier of 16 kcal/mol for the association of the periplasmic Hg 2+ ‐bound protein MerP with MerF and 7 kcal/mol for the subsequent association of MerF's two cysteine pairs. Despite the significant conformational changes required to move the binding site across the membrane, coarse‐grained simulations of multiple copies of MerF support the expectation that it functions as a monomer. Our results demonstrate how conformational changes and binding thermodynamics could lead to such a small membrane protein acting as an ion transporter. Published 2019. This article is a U.S. Government work and is in the public domain in the USA. Abstract : Mercury‐resistant bacteria import Hg 2+ ions across the cytoplasmic membrane by means of the two‐transmembrane‐helix transport protein MerF. The authors have characterized the dynamics and energetics of MerF using molecular dynamics simulations and free‐energy calculations. They find that the conformation of MerF is adaptable, shifting to receive the ion from the periplasm and deliver it to the cytoplasm. The results reveal how such a small protein can transport mercury across the membrane.